BASIC TERRITORIES AND RESOURCES OF TOURISM DEVELOPMENT IN TEHRAN PROVINCE OF IRAN: (Islamic Republic of Iran) (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
In the article natural, historical-cultural and human-made tourist attractions of Tehran province have been analyzed for tourist usage and distribution. The role of tourist resources for forming and developing of basic tourist territories and destinations is given.
Keywords: natural; historical-cultural attractions; human-made attractions